The number of parathyroid glands preserved during thyroidectomy and relationship between hypoparathyroidism - Sidhic, Kummankandath Abbas; Hisham, Yousef; Nabeel, Thommil Padinjarenalakath; Ali Abid, Karat Prambil (International Surgery Journal, 2017)
Background: The aim of the study was to determine the number of parathyroid glands that need to be preserved to prevent hypoparathyroidism and to understand the relation between the number of parathyroid glands preserved and hypoparathyroidism. Methods: A retrospective study was performed on 350 patients who had undergone trans cervical total thyroidectomy with or without neck dissection for papillary thyroid carcinoma between July 2010 to August 2015. Results: Incidental parathyroidectomy occurred in 19.1% of patients, one parathyroid gland in 17.8%, two in 2% and 3 in 0.5%. Transient hypoparathyroidism increased when incidental parathyroidectomy occurred on multivariate regression analysis, but it was not influenced by the actual number of parathyroid glands removed. There was no relationship between the number of parathyroid glands preserved and hypoparathyroidism. Conclusions: It is not compulsorily required to prevent permanent hypoparathyroidism, but the preservation of all the four parathyroid glands during thyroidectomy decreases the incidence of transient hypoparathyroidism. When auto transplantation is not performed, to prevent permanent hypoparathyroidism, preserving at least one parathyroid gland with an intact blood supply is sufficient.